Audit Tata Kelola TI pada BMKG dengan Menggunakan Framework COBIT 2019 Studi Kasus: BMKG Wilayah III Denpasar - Aprianingsih, Ade Irma; Githa, Dwi Putra; Sasmita, Gusti Made Arya (Universitas Multi Data Palembang, 2024)
The development of science and technology is currently constant along with increasingly modern developments. Technology today has become something or could be said to be an important need in people's daily lives. COBIT is a framework developed by ISACA for IT-related management and control in an organization to maximize the use of IT. Several problems that often occur in organizations often cause a decline in the quality of governance in BMKG Region III Denpasar, so it is necessary to carry out an audit of information technology governance. This IT governance audit research uses COBIT 2019 as a framework that can help organizations maintain high quality information by supporting organizational decision making. In this research, process domains APO13, BAI01, and BAI10 were obtained. Therefore, the ability level value obtained in the APO13 process domain is located at level 2, BAI01 is located at level 2, and BAI10 is located at level 2. So, the GAP value obtained from each of these domains is 3.